Life in abundance : studies of John's Gospel in tribute to Raymond E. Brown, S.S. - Brown, Raymond Edward; Donahue, John R. (Collegeville, Minn. : Liturgical Press, 2005)
"Primarily a collection of essays (originally papers) and responses given at 'An International Conference on the Gospel of John: Life in Abundance,' held at St. Mary's Seminary and University in Maryland, October 16-18, 2003; the book includes presentations of Johannine theology, issues of interpretation, considerations of the work of Raymond Brown, and two homilies"--Provided by publisher.
Includes bibliographical references (p. 259-289) and indexes.
Keywords: Brown, Raymond Edward -- Congresses; Bible. -- Criticism, interpretation, etc. -- Congresses